Development of conceptual bases of state regulation for balanced and sustainable development of the agri-food sector - Кулаковська, Тетяна Анатоліївна (Technology audit and production reserves, 2016)
The basic problems of low efficiency of state regulation for development of the agri-food sector in Ukraine are considered in the article. The studies established the main disadvantages of state regulation for development of the agri-food sector in Ukraine: lack of consistency in the application of state regulation; lack of complexity in the direction of supporting the development of the agri-food sector (agricultural producers, processors and consumers); lack of coordination of the state action to promote and regulate the development of the agri-food sector with periods of economic development; corruption and bribery in the bodies of provision and distribution of state funds allocated for the support of agricultural producers, and so on. New conceptual bases of state policy for regulation and support the development of the agri-food sector are developed, including the expediency of state regulation of agricultural markets on the value chain; obligation of refusal of non-subsidized approach in support of the agricultural sector with the transition to regulation of development, taking into account the cyclical development of the mechanism of the economic system, and others. All proposed measures are aimed at improving the efficiency of the state agrarian policy.